EFEKTIVITAS PELATIHAN “I’M POSSIBLE” UNTUK PENINGKATAN KESIAPAN KERJA MAHASISWA UP45 - Femmy Lekahena; Ayu Gigih Rizqia; Maliqazuhra Iqbal (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
University has strategic role in producing high quality graduates who are ready to enter the world of work. However, in reality, there are many graduates who experience difficulties in entering the workforce due to low work readiness, which contributes to unemployment rates. This study aims to test the effectiveness of I’m Possible training, an intervention that focuses on improving the work readiness of students at Universitas Proklamasi 45 (UP45). The study population was 670 students, with 22 participants selected using purposive sampling techniques based on moderate and low work readiness scores. The analysis method using the Wilcoxon Rank Test showed significant results (statistical value = 235,000; p < 0.01), which means that the I'm Possible training is effective in increasing work readiness. These findings recommend that university must integrate work readiness development programs into the curriculum and encourage students to develop an optimistic and responsible attitude in planning their future. Keywords: I’m Possible, Optimism, Work Readiness, College Student